2022
DOI: 10.15359/ree.26-1.21
|View full text |Cite
|
Sign up to set email alerts
|

Errores y dificultades en la elaboración de las tesis de pre y postgrado del estudiantado peruano: Implicaciones pedagógicas

Abstract: Objetivos. Describir las dificultades reportadas por el estudiantado en el proceso de elaboración de su trabajo de grado y describir los errores cometidos. Metodología. Se realizó una investigación de diseño documental que incluyó una muestra de tesis (n = 120) presentadas para obtener distintos grados académicos entre 2018 y 2019. Se buscó información sobre errores de fondo (unidad, demostración y profundidad) y de forma (presentación, redacción y ortografía, utilización de normas para la inclusión de citas y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
2
Order By: Relevance
“…In Peru, due to different research initiatives and university teams (Castro-Rodríguez and Pares-Ballasco, 2022), there has been a significant increase in research in recent years (Glass et al, 2018;Gualdrón Frías et al, 2019). However, there are still challenges and errors in the development of research projects (Soto, 2020;Perdomo and Morales, 2022). Therefore, in light of the need for evaluation tools to investigate the effects of distractors on research, the objective of this research was to adapt and validate the distractors scale of research tasks in Peruvian university students (Appendix).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Peru, due to different research initiatives and university teams (Castro-Rodríguez and Pares-Ballasco, 2022), there has been a significant increase in research in recent years (Glass et al, 2018;Gualdrón Frías et al, 2019). However, there are still challenges and errors in the development of research projects (Soto, 2020;Perdomo and Morales, 2022). Therefore, in light of the need for evaluation tools to investigate the effects of distractors on research, the objective of this research was to adapt and validate the distractors scale of research tasks in Peruvian university students (Appendix).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the importance of these scientific products, university students have found problems in successfully completing their research processes, mainly due to time issues (Perdomo and Morales, 2022), lack of mastery of the research methodology, and absence of motivation (Soto, 2020), among other factors. This has led to many of these research works being only presented in academic research days (Magariño-Abreus et al, 2021;Castro-Rodriguez and Pares-Ballasco, 2022), which are more in line with a final course evaluation context, while very few are presented and published in indexed scientific journals (Carvajal Tapia and Carvajal Rodríguez, 2018;Gualdron et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a study about research at a university in the Philippines, Pangket et al (2023) mention that students lacked research skills and had different activities that made it difficult for them to carry out their research work. In addition, Perdomo & Morales (2018) in a mixed-methods study that consisted of thesis reviews reported that there were difficulties associated with research and academic writing skills (p. 4), as well as difficulties in how to use references in APA or Vancouver style; and attitudes towards statistics and research methodology skills (Capa-Luque et al, 2022, p. 217).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the aspects of research courses, thesis advisors, and thesis advising must be regulated, especially in terms of research experience. This is because some students revealed that advisors had little experience in scientific research and had to approach it from a methodological and formal point of view, according to Perdomo & Morales (2018). These authors also concluded that advisors' trajectory must be verified by their scientific productivity and the communication of their results.…”
Section: Introductionmentioning
confidence: 99%
“…competencias en el pregrado (Sosa, 2022;Palacios, 2021), incitando a la mejora continua de los productos académicos que de aquello emanan y dentro de los cuales los seminarios de finalización de grado representan su instancia pivote (Perdomo & Morales, 2022;Venegas et al, 2016).…”
unclassified